2014
DOI: 10.1007/s00216-014-8114-z
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-based algorithm allows correction for the hematocrit bias in quantitative analysis of caffeine and its major metabolite in dried blood spots

Abstract: Although dried blood spot (DBS) sampling is increasingly receiving interest as a potential alternative to traditional blood sampling, the impact of hematocrit (Hct) on DBS results is limiting its final breakthrough in routine bioanalysis. To predict the Hct of a given DBS,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 9 publications
3
31
1
Order By: Relevance
“…the sum of all feature peak integrals per subject, and hematocrit. Here, we measured K + concentrations of DBS extracts as proxies for hematocrit (Capiau et al 2013; De Kesel et al 2014). As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the sum of all feature peak integrals per subject, and hematocrit. Here, we measured K + concentrations of DBS extracts as proxies for hematocrit (Capiau et al 2013; De Kesel et al 2014). As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As validation of our methodology, we performed an untargeted analysis to pinpoint metabolites that were statistically associated with population characteristics. Our untargeted workflow includes: 1) data filtering and normalization for potassium levels as surrogates for hematocrit (Capiau et al 2013; De Kesel et al 2014), 2) multivariate statistical analysis to identify discriminating features, 3) manual examination of significant features for peak and integration quality, and 4) annotation of significant features with MSMS.…”
Section: Introductionmentioning
confidence: 99%
“…Because the biological factor of interest is breastfeeding, two fatty acids that are abundant in breast milk, i.e., palmitoleic acid and docosahexaenoic acid (DHA) (Chuang et al, 2013;Gardner et al, 2017), were used as positive controls, selected prior to any analysis. Known sources of technical variation in these samples include NBS age, potassium level (a measure of hematocrit), run-order, and batch (De Kesel et al, 2014;Pupillo et al, 2016).…”
Section: Metabolomics Of Neonatal Blood Spotsmentioning
confidence: 99%
“…Capiau et al recently demonstrated use of the measurement of potassium (K) from DBS sub-punches to estimate HCT [5]. This procedure has been used successfully to correct for effects of HCT in DBS analysis [6,7].…”
Section: Introductionmentioning
confidence: 97%